Contornos discursivos do antipetismo nas mídias sociais: uma análise a partir do Movimento Brasil Livre - Caldara, Marcus Vinicius Calderan (Universidade Federal de São Carlos, 2020)
This job pursuit to explore the existing relationships between the relative popularization of information technologies and social media and the growing “polarization” in the taken of political positions in Brazil, and how these relationships imply transformations in the strategies for the circulation of information by a segment of groups and political actors. Theoretically guided by a relational conception of political conflict, which directly affects the design of positions in the space of ideological production, the general objective of the research is to articulate the modalities of the antipetism (a polysemic signifier) ​​conveyed by the Movimento Brasil Livre (MBL) within your social media.
Contornos discursivos del antipetismo en las redes sociales: un análisis del Movimiento Brasil Libre
Keywords: antipetismo; nova-direita; redes sociais; indústria cultural; polarização política; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA DO CONHECIMENTO